Representation of Locality in Media Art in Yogyakarta: Dedy Shofianto's Kinetic Art Case Study - Wicaksono, Satrio Hari (Institut Seni Indonesia Yogyakarta, 2024)
In the development of contemporary art, the issue of identity becomes a central and important thing to be studied more deeply, especially the personal or communal identity of marginalized parties in the context of modern society. This is what makes local values elevated and become a specific, unique identity character and become the characteristic of the artist in his work. Similarly, artists in Indonesia form a qualified personal representation with specific local values based on their background. Not just dwelling on conventional media, artists explore media more broadly. New media such as digital devices, kinetics, sound and so on are felt to be able to represent the state of the surrounding environment without abandoning the local identity that remains attached. Dedy Shofianto is one of the Yogyakarta artists whose execution uses conventional media but with a different approach, where kinetic elements become an identity that is closely related to the artist, which is supported by a strong local content narrative. The visual representation and material characteristics carried have a background and cultural narrative that is a unique characteristic of each of Shofianto's works, such as the use of wood materials that are attached to Indonesia as a tropical country and the myths of the archipelago are visible representations in Shofianto's works.Dalam perkembangan seni kontemporer, persoalan identitas menjadi hal yang pokok dan penting untuk dikaji lebih mendalam, khususnya identitas personal atau komunal dari pihak yang terpinggirkan dalam konteks masyarakat modern. Hal ini yang membuat nilai-nilai lokal terangkat dan menjadi karakter identitas yang spesifik, unik dan menjadi penciri yang khas dari sang seniman dalam karyanya. Begitu pula seniman-seniman di Indonesia yang membentuk representasi personal yang syarat dengan nilai-nilai lokal spesifik berdasar latar belakang mereka. Tak sekedar berkutat di media konvensional, para seniman mengeksplorasi media secara lebih luas. Media-media baru seperti perangkat digital, kinetik, suara dan lain sebagainya dirasa mampu merepresentasi dengan keadaan lingkungan di sekitar tanpa menanggalkan identitas lokal yang tetap melekat. Dedy Shofianto adalah salah satu seniman Yogyakarta yang eksekusi kekaryaannya menggunakan medium konvensional namun dengan pendekatan yang cenderung berbeda, dimana unsur kinetik menjadi identitas yang lekat dengan sang seniman, yang didukung dengan narasi muatan lokal yang kuat. Representasi visual dan karakteristik material yang diusung memiliki latar belakang dan narasi kultural yang menjadi ciri khas unik dari masing-masing karya Shofianto, seperti penggunaan material kayu yang lekat dengan Indonesia sebagai negara tropis dan mitos-mitos nusantara menjadi representasi yang terlihat dalam karya-karya Shofianto.